The Culinary Construction of Identity: Negotiating Korean American Immigrant Subjectivity in Zauner’s Crying in H Mart (Rainbow: Journal of Literature, Linguistics and Culture Studies, 2026)
This study investigates the role of food as the representation of Korean American identity in the memoir Crying in H Mart by Michelle Zauner. The role of food as a cultural practice within a transnational context has been less studied than grief and emotional experience in the memoir. This study aims to examine how food serves as a means of sustaining and reconstructing cultural identity, memory, and a sense of belonging across different places. Employing a qualitative approach, the study focuses on analyzing the food narratives using the lens of close reading and interpreting them with the notion of transnationalism presented by Ulf Hannerz, specifically interconnectedness and mobility of meanings. The analysis suggests that the foods mentioned serve a purpose beyond simply sustaining life.  Additionally, food was a means of preserving cultural heritage and remembering the past across multiple locations. Soy sauce, eggs, kimchi, sesame oil and cold radish soup are all dishes closely related to family tradition, intergenerational knowledge heritage and daily cultural activities. The study also reveals that H Mart functions as a transnational cultural space where individuals reconnect with cultural memories, identity, and a sense of belonging. Cultural meanings are constantly negotiated rather than established as a result of distance, loss, and attempts to maintain cultural links. The memoir demonstrates that Korean American identity is continuously shaped through everyday interactions with food, memory, and cultural practices. This study extends previous scholarship by showing that food functions as a transnational cultural practice that sustains identity across national boundaries.